2006
DOI: 10.21836/pem20060402
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the clinical efficacy, safety and palatability of meloxicam (Metacam) treatment in horses with musculosceletal disorders

Abstract: SummaryThis GCP(v) multi centre blinded positive controlled study investigated under field conditions the clinical efficacy, safety and palatability of meloxicam in horses suffering from musculoskeletal disorders. The efficacy of meloxicam (Metacam ® ) at the recommended dose of 0.6 mg/kg body weight administered once daily was investigated (n=100) in comparison to vedaprofen (Quadrisol ® , n=97). Lameness at a trot, walk and rest was recorded before initiation of therapy on Day 1, after a 5, 10 or 14 day tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 6 publications
0
27
1
2
Order By: Relevance
“…In contrast, Kelley and Curtis (1978) found higher RT in primiparous sows during farrowing, but not from the birth of the last piglet until 3 or 4 days post partum. Although meloxicam treatment increased feed and water intakes in calves with neonatal calf diarrhoea complex (Todd et al, 2010), and improved feed intake in pigs with non-infectious locomotor disorders (Friton et al, 2003), in comparison with placebo treatment, no effect was found in this study in the appetite of the sows after farrowing. It is, however, difficult to objectivate an increase in feed consumption in sows just after farrowing, especially in primiparous sows.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In contrast, Kelley and Curtis (1978) found higher RT in primiparous sows during farrowing, but not from the birth of the last piglet until 3 or 4 days post partum. Although meloxicam treatment increased feed and water intakes in calves with neonatal calf diarrhoea complex (Todd et al, 2010), and improved feed intake in pigs with non-infectious locomotor disorders (Friton et al, 2003), in comparison with placebo treatment, no effect was found in this study in the appetite of the sows after farrowing. It is, however, difficult to objectivate an increase in feed consumption in sows just after farrowing, especially in primiparous sows.…”
Section: Discussioncontrasting
confidence: 67%
“…Meloxicam, an NSAID of the oxicam class, acts by inhibiting prostaglandin synthesis (Engelhardt and Trummlitz, 1990) and inducible cyclo-oxygenase-2 (COX-2; Engelhardt, 1996), thereby exerting anti-inflammatory, antitoxic, antiexudative, analgesic and antipyretic effects (Friton et al, 2006). Meloxicam is used for noninfectious locomotor disorders in pigs, by reducing the signs of lameness and inflammation (Friton et al, 2003), the porcine respiratory disease complex in growing pigs (Georgoulakis et al, 2006) and for the relief of post-operative pain associated with minor soft tissue surgery such as castration (Keita et al, 2010). In sows, meloxicam is used as an adjunctive therapy in the treatment of mastitis-metritis-agalactia syndrome (MMA) with appropriate antibiotic drugs (Hirsch et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Mustonen et al (123) looked at two doses of oral ketoprofen compared to a placebo to treat non-infectious lameness, which they scored on a 5-point scale from no lameness to severe lameness. Both studies saw a significant improvement with drug treatment, compared with the placebo (122, 123). Nonetheless, some caution is needed, as locomotor disorders do not necessarily result in pain, with individuals possibly affected by a biomechanical abnormality in the absence of pain.…”
Section: Pain Assessment In Pigsmentioning
confidence: 90%
“…A clinical lameness score, combining lameness at rest and at walk, was used to assess the efficacy of an intramuscular injection of meloxicam compared to a placebo to treat non-infectious locomotor disorders (122). Mustonen et al (123) looked at two doses of oral ketoprofen compared to a placebo to treat non-infectious lameness, which they scored on a 5-point scale from no lameness to severe lameness.…”
Section: Pain Assessment In Pigsmentioning
confidence: 99%
“…If the pain cannot be effectively treated, culling may be the only practical option in pig farming [18]. Thus, the therapy of lame piglets ought to include measures aimed to decrease pain and thereby also minimize any adverse effect on feed intake [19]. …”
Section: Introductionmentioning
confidence: 99%